2018
DOI: 10.3389/fphar.2018.00617
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polyphenols From Campomanesia adamantium on Platelet Aggregation and Inhibition of Cyclooxygenases: Molecular Docking and in Vitro Analysis

Abstract: Campomanesia adamantium is a medicinal plant of the Brazilian Cerrado. Different parts of its fruits are used in popular medicine to treat gastrointestinal disorders, rheumatism, urinary tract infections and inflammations. Despite its widespread use by the local population, the mechanisms involving platelet aggregation and the inhibition of cyclooxygenase by C. adamantium are unknown. This study evaluated the chemical composition, antioxidant activities and potential benefits of the C. adamantium peel extract … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 65 publications
(82 reference statements)
2
17
0
2
Order By: Relevance
“…This is in agreement with previous reports showing that myricetin strongly inhibited collagen- (Dutta-Roy et al, 1999) and arachidonic acid-evoked platelet aggregation (Lescano et al, 2018). Interestingly this latter work reported that myricetin does not inhibit cyclooxygenase activity in platelets (Lescano et al, 2018). It has been described that gallic acid is able to inhibit platelet aggregation only at exceedingly high concentrations (Chang et al, 2012) which is corroborated by our data showing no effect below 300 mM.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This is in agreement with previous reports showing that myricetin strongly inhibited collagen- (Dutta-Roy et al, 1999) and arachidonic acid-evoked platelet aggregation (Lescano et al, 2018). Interestingly this latter work reported that myricetin does not inhibit cyclooxygenase activity in platelets (Lescano et al, 2018). It has been described that gallic acid is able to inhibit platelet aggregation only at exceedingly high concentrations (Chang et al, 2012) which is corroborated by our data showing no effect below 300 mM.…”
Section: Discussionsupporting
confidence: 94%
“…Myricetin inhibited platelet aggregation and activation induced by agonists of the collagen and thrombin pathways, whereas gallic acid showed little to no effect even at 10× higher concentrations. This is in agreement with previous reports showing that myricetin strongly inhibited collagen- (Dutta-Roy et al, 1999) and arachidonic acid-evoked platelet aggregation (Lescano et al, 2018). Interestingly this latter work reported that myricetin does not inhibit cyclooxygenase activity in platelets (Lescano et al, 2018).…”
Section: Discussionsupporting
confidence: 94%
“…In this study, we investigated the maintenance effect of myricetin against human hepatocyte functional capacity and its involvement in the MAPK pathways. Myricetin showed antioxidative, cytoprotective, anti-carcinogenic, antimicrobial, and anti-platelet properties [12,15,[32][33][34], which are all beneficial for cell engraftment. We hope the results presented here will help to demonstrate that myricetin treatment has the potential to make a significant contribution to the development of cell transplantation therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Peel extract of Campomanesia adamantium (Cambess.) O. Berg showed antiaggregatory effect in platelet aggregation assay induced by arachidonic acid at 2.5 g L -1 concentration (8.2 mmol L -1 of quercetin equivalent) (43). This was attributed to quercetin and myricetin.…”
Section: Mechanisms Of Antiplatelet Action Of Individual Flavonoids Hmentioning
confidence: 90%